Levetiracetam and cutaneous adverse reactions: A systematic review of descriptive studies. (February 2020) - Rashid, Muhammed; Rajan, Asha K; Chhabra, Manik; Kashyap, Ananth
Highlights: Levetiracetam is a widely used anti-epileptic drug. Rash, acanthosis, hyper pigmentation, purpura, and ulceration were major reactions. Withdrawal of drug and symptomatic treatment is effective in management of reaction. The current evidence will be helpful in routine practice of healthcare practitioners. Abstract: Purpose: Recently, there have been an increased number of reports on levetiracetam (LEV) induced cutaneous adverse drug reactions (CADRs). We aimed to identify and critically evaluate all the descriptive studies on LEV induced-CADRs and to describe the possible clinical manifestations, management, and treatment outcomes of the condition. Methodology: PubMed and grey literature databases were searched from inception to June 2019 without any restriction. We also performed a bibliographic search for additional studies. Only descriptive studies on LEV-induced CADRs were included for our review. Study selection, data abstraction and quality assessment were performed by two contributors independently and disagreements were settled through consensus or through discussion with a third reviewer. Results: Data from 24 out of 88 studies, which included 25 patients (12 female and 13 male) aged from 40 weeks to 73 years, were reviewed. Patients received between 500 mg/day to 3000 mg/day of LEV. Drug reaction with eosinophilia and systemic symptoms syndrome, Steven-Johnson syndrome, toxic epidermal necrolysis, acute generalised exanthematous pustulosis, generalised hyperpigmentation and leucocytoclastic vasculitis were observed among the included patients. Immediate cessation of LEV, providing supportive care and use of topical antihistamines and anti-inflammatory drugs appeared to be the mainstay of management, and all patients were found to have recovered. Conclusion: Clinicians should be aware of the possible CADRs induced by LEV to avoid the development of a potentially fatal condition. Immediate withdrawal of the drug and supporting care seem to be effective in the management of the CADRs. Registration number: International Prospective Register for Systematic Reviews (PROSPERO) number CRD42019141002.